2020
DOI: 10.1017/s0021932020000371
|View full text |Cite
|
Sign up to set email alerts
|

Addressing reproductive health knowledge, infertility and coping strategies among rural women in India

Abstract: An awareness of fertility and the factors affecting it is crucial to dealing with infertility, though little research has been conducted in the context of rural India. This study assessed Indian women’s perceived causes of, and strategies for coping with, infertility and the associations with levels of reproductive health knowledge in rural areas. Primary data were collected through mapping and listing in high infertility prevalence districts of West Bengal in 2014–15. A total of 159 women aged 20–49 years who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…A higher proportion of the respondents want their treatment free of cost ( 32 ). Further, wide disparities exist in the availability, quality, and delivery of infertility services between the developed and developing nations, as well as between the two regions of the same country ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher proportion of the respondents want their treatment free of cost ( 32 ). Further, wide disparities exist in the availability, quality, and delivery of infertility services between the developed and developing nations, as well as between the two regions of the same country ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…30,[31][32][33][34][35][36][37][38][39][40], and >40 years); age at marriage (<18 and =>18 years); >20 years); age gap between husband and wife (1-3, 4-6, 7-9, >9 years); level of education (illiterate, 1-4 years/primary, 5-8 years/middle or upper primary and 9-10 years/secondary and higher secondary, >12 years/graduate and above); husband's level of education (as for the respondents); respondent's media exposure (not exposed and exposed, i.e., whether she had received any information on fertility and treatment-related issues from any kind of media); respondent's work status (never worked and ever worked); religion (Hindu and Muslim); caste (Scheduled caste/SC, Scheduled tribe/ST and Other Backward Caste/ OBC and General/open); monthly income (<=5,000, 6,000-10,000, 11,000-15,000, >15,000 rupees); type of treatment women received (allopathic, AYUSH, traditional/home remedies/religious remedies; type of village women belong to (village with PHC, village with SC, village with no government health facility).…”
mentioning
confidence: 99%
“…[ 5 17 30 31 32 33 34 ] Only three studies conducted in rural India revealed results lesser than 20%. [ 6 12 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies by The World Health Organization indicate that the current prevalence of infertility is about 9% [ 1 ]. Some scholars believe that the prevalence of infertility is an “iceberg phenomenon” and that most couples suffering from infertility are still undiagnosed [ 2 ]. Infertility not only causes greater psychological and social pressure on the couple, but also has an impact on the stability of society [ 3 ].…”
Section: Introductionmentioning
confidence: 99%